Developments in the performance of the Malaysian banking sector: opportunity cost of regulatory compliance - Sufian, Fadzlan (Inderscience Publishers, 2010)
By using bank-level data, this paper examines how regulation and supervision affects the profitability of the Malaysian banking sector over the period 1992–2003. The empirical findings suggest that Malaysian banks with higher liquidity levels, credit risk and overhead expenses exhibit lower profitability level. On the other hand, banks with a higher proportion of income from non-interest sources and better-capitalised exhibit higher profitability level. The results suggest that economic growth and inflation has positive impact on the profitability of the Malaysian banking sector. The empirical findings suggest that the impact of regulation and supervision is negatively related to bank profitability.